2012
DOI: 10.1016/j.ausmj.2011.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Regional Differences in Chinese Consumer Acceptance of New Mobile Technology: A Qualitative Study

Abstract: This study examines consumer adoption of 3G mobile technology in China. The qualitative study involved 45 in-depth interviews undertaken in three major Chinese cities to explore the beliefs and attitudes which determine Chinese consumers’ acceptance of the mobile technological innovation. The findings are compared and contrasted against those reported in Western studies. The variations underpinning adoption of 3G between consumers in the three regional cities were identified. Specifically, it was found that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Zhang, Guo, and Chen (2011) showed that social influence was important on adoption and use behavior of IT based on an extended model derived from the TAM. It was found that the regions differed in terms of the relative importance of the identified adoption determinants such as perceived social outcomes for using the innovation and the effects of social influence on the adoption (Song, Drennan, & Andrews, 2012). Thus, we propose the following hypothesis:…”
Section: Social Influencementioning
confidence: 96%
“…Zhang, Guo, and Chen (2011) showed that social influence was important on adoption and use behavior of IT based on an extended model derived from the TAM. It was found that the regions differed in terms of the relative importance of the identified adoption determinants such as perceived social outcomes for using the innovation and the effects of social influence on the adoption (Song, Drennan, & Andrews, 2012). Thus, we propose the following hypothesis:…”
Section: Social Influencementioning
confidence: 96%
“…Users tend to use a product or service again if it matches their habitual needs or wants and can fulfill their values. This idea is categorized as COMP, a dimension of IDT (Song et al, 2012). Consumers in gaming face problems related to moving out of a problematic level or may sometimes be unable to complete the gameplay activity.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…It involves the development of strong relationships between exchange partners that enhance satisfaction, trust, value, commitment, and loyalty and ultimately improve profitability (Jain et al, 2018; Palmatier et al, 2006; Weaven et al, 2017). Although there is increasing research in consumer or business management acceptance of new technologies (Barnes & Cumby, 2002; Song et al, 2012), the impact of technologies on relationship marketing is often not adequately investigated, leading to overstated hypothetical predictions of its future potential (Bilgihan & Bujisic, 2015; Hart et al, 2000). Moreover, there are a number of new technologies available each year, for example, blockchain technology, automation solution‎, information technology management, and customer relationship management (CRM), among others (Khodakarami & Chan, 2014; Kumar & Reinartz, 2018).…”
Section: Overviewmentioning
confidence: 99%